2015
DOI: 10.1002/nau.22924
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐rater reliability and diagnostic accuracy of a new vaginal dynamometer to measure pelvic floor muscle strength in women with urinary incontinence

Abstract: Our results suggest that this new vaginal dynamometer is a reliable and valid instrument for quantifying PFM strength. Neurourol. Urodynam. 36:333-337, 2017. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(69 citation statements)
references
References 37 publications
(68 reference statements)
4
61
0
Order By: Relevance
“…Our results showed good ( r 2 = 0.75) agreement between manometry and dynamometry, when peak values are used, which suggests that both are suitable tools for measuring PFM strength during maximum contraction efforts performed by women with PFD. Non‐commercial dynamometry has previously been investigated . Consistent with our results, Morin et al reported a Pearson's correlation ( r s ) of 0.564 between modified Oxford Grading Scale and dynamometry, and found lower correlation values in incontinent than in continent women ( r s = 0.450 vs r s = 0.727).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed good ( r 2 = 0.75) agreement between manometry and dynamometry, when peak values are used, which suggests that both are suitable tools for measuring PFM strength during maximum contraction efforts performed by women with PFD. Non‐commercial dynamometry has previously been investigated . Consistent with our results, Morin et al reported a Pearson's correlation ( r s ) of 0.564 between modified Oxford Grading Scale and dynamometry, and found lower correlation values in incontinent than in continent women ( r s = 0.450 vs r s = 0.727).…”
Section: Discussionsupporting
confidence: 90%
“…Vaginal palpation 1,8,9,[14][15][16][17][18][19] is inexpensive and is used widely in clinical practice to evaluate the quality, power, and endurance of PFM contractions. However, it is subjective and has poor interrater reliability.…”
mentioning
confidence: 99%
“…Intravaginal dynamometry is recognized as an optimal tool to quantify active and passive pelvic floor tissue properties . Relative measures of PFM force generating capacity acquired by intravaginal dynamometry have demonstrated excellent reliability and correlate strongly with manual measures of PFM strength, the current standard for clinical assessment of the female PFMs. Further, automated intravaginal dynamometry yields objective, continuous, and high‐resolution measures—a necessity if clinicians wish to monitor pelvic floor dysfunction arising from injury or improvements in PFM function resulting from physical therapy or other interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Among clinicians, the most typical method for quantification of PF function is digital palpation because it is fast, requires no equipment, and selectively depicts PFM activity better than most available biofeedback devices (Peschers et al 2001b Several manometers van Raalte and Egorov 2015;Ribeiro et al 2016), dynamometers (Dumoulin et al 2004a;Saleme et al 2009;Chamochumbi et al 2012;Romero-Cullerés et al 2017) and EMG techniques Ptaszkowski et al 2015) have been proposed to objectively quantify PF function. However, most of these methods were developed for research purposes, in contrast to the proposed sensor, which is already commercially available and has the advantage of differentiate the effects of maximum contraction of PFMs as opposed to an increase in intra-abdominal pressure (Valsalva) along the vaginal canal (Fig.3).…”
Section: Discussionmentioning
confidence: 99%
“…Most authors suggest assessing PFM strength using vaginal dynamometers, considering it a better method as they measure force directly Verelst and Leivseth 2004a;Saleme et al 2009;Nunes et al 2011;Ashton-Miller et al 2014;Parkinson et al 2016;Romero-Cullerés et al 2017). However, none of the aforementioned dynamometer prototypes are available to be commercialized, and they appear to be used only in a research scenario.…”
Section: Rational For the Development Of A New Measurement Device Of mentioning
confidence: 99%